PERBANDINGAN HASIL PEMERIKSAAN TROMBOSIT YANG SEGERA DIPERIKSA DAN DITUNDA 60 MENIT PADA MAHASISWA PRODI DIII ANALIS KESEHATAN - Fatma Fatma; Rosa Devitria; Elvina Elvina (Ensiklopedia of Journal, 2026)
Platelet count examination is one of the important examinations in hematology to help diagnose bleeding disorders. Delaying the examination after blood sampling can affect the results of platelet examination because platelets have the ability to aggregate and adhere. This study aimed to compare platelet count results from immidiate versus 60-minute delays in D-III Health Analyst. The study used a completely randomized experimental design on 15 venous blood samples with EDTA anticoagulant. The examination was carried out using a Dirui BCC 3600 hematology analyzer. The results showed that the average platelet count in the immediate examination was 276,800 cells/mm³ of blood, while in the examination that was delayed for 60 minutes the average was 272,333 cells/mm³ of blood. The results of statistical analysis using the t-dependent test showed a significant difference with a value of p = 0.003 (p 0.05), which indicates that delaying the examination for 60 minutes causes a significant decrease in platelet count results. Based on the results of this study, it is recommended that platelet examination be carried out immediately after sampling to obtain accurate results.Keywords: Platelets, Delayed Examination, EDTA